Teaching Magnetism to Preschoolers through ICT: An Early Childhood Science Approach - Skothou, Stavroula; Trapali, Maria (European Scientific Journal, ESJ, 2025)
This publication aims to explore the introduction of scientific concepts during preschool age, focusing specifically on the natural sciences and the concept of magnetism. The properties and types of magnets were chosen as the central theme based on the children’s interests. The educational process began with a series of structured activities designed by the educator, followed by the integration of Information and Communication Technologies (ICT), including educational software and interactive tools used by the children. A key element of the approach was the creation of an improvised story-a fairy tale scenario-that served as a springboard for the implementation of the activities. Through the use of ICT, children were encouraged to explore and verify the concepts of magnetism and magnet properties. The use of these digital tools played a crucial role not only in reinforcing previously acquired knowledge but also in introducing new technological challenges that further enhanced the educational process. In conclusion, the integration of storytelling, hands-on activities, and ICT in teaching magnetism at the preschool level demonstrates the effectiveness of technology in enhancing engagement, understanding, and knowledge retention in early childhood science education. The evidence indicates that the integration of structured educational activities with Information and Communication Technologies (ICT) proved to be an effective approach for enhancing preschool children’s conceptual understanding of magnetism. Increased engagement and active participation were observed, as storytelling and play-based methods facilitated the comprehension of core scientific concepts, such as the properties and types of magnets. ICT tools supported experiential learning by enabling children to explore, experiment, and verify acquired knowledge. Improvements were noted in observation skills, the formulation of simple hypotheses, and the ability to draw basic conclusions. Overall, the pedagogical design-enriched through the use of digital technologies, yielded positive learning outcomes and contributed significantly to the development of early scientific thinking within a preschool education context.